STUDIES ON PLANT HYPERTENSINASE - Gollan, Frank (The Rockefeller University Press, 1948)
Many plants contain an enzyme similar in most biological properties to the hypertensinase obtained from blood and some animal tissues, notably kidney and intestinal mucosa. Wheat bran is a rich source of the plant hypertensinase, and from it a potent, non-toxic preparation was made by the use of isoelectric and ammonium sulfate precipitation as the means of purification. Hypertensinase derived from bran and administered intramuscularly was not absorbed, or was absorbed only very slowly, into the blood plasma. Repeated intramuscular injection of large quantities of plant hypertensinase did not reduce the blood pressure of dogs with experimental renal hypertension. The intravenous injection of large quantities of plant hypertensinase into dogs resulted in an immediate increase in the content of hypertensinase in the plasma. Dogs with a high hypertensinase level in the plasma failed to react, or reacted much less markedly to the intravenous injection of amounts of renin or hypertensin which had previously proved effective. The slow intravenous injection of plant hypertensinase into a dog with experimental renal hypertension reduced the blood pressure to the normal level for the period during which the concentration of plant hypertensinase in the blood was considerably elevated. After the return of the hypertensinase of the plasma to normal, the blood pressure rose again to its previously high level. Inactivated plant hypertensinase did not increase the hypertensinase content of the plasma, did not interfere with the action of renin and hypertensin, and did not reduce the high blood pressure of dogs with experimental renal hypertension. In a dog with an increased level of plasma hypertensinase, the pressor substance hypertensin could still be detected in the systemic blood immediately after the intravenous injection of renin in an amount to which the animal responded with only a slight rise in blood pressure.